Biological Evaluation of Pupalia lappacea for Antidiabetic, Antiadipogenic, and Hypolipidemic Activity Both In Vitro and In Vivo - Vivek Kumar; Parag Jain; Kalpana Rathore; Zabeer Ahmed (Scientifica)
Objective. The present study assesses the effect of Pupalia lappacea (L.) Juss. (Amaranthaceae) (PL) leaves ethanolic extract on adipocytes, blood glucose level, and lipid level in streptozotocin (STZ) induced diabetic rats. Materials and Methods. Male Albino rats were rendered diabetic by a single moderately sized dose of STZ (45 mg/kg, intraperitoneally) at once before starting the treatment. Animals were divided into five groups: normoglycemic control, diabetic control, reference group (glibenclamide, 5.0 mg/kg), AS001 (250 mg/kg extract), and AS002 (500 mg/kg extract) each containing six animals for in vivo study. Antidiabetic and hypolipidemic activity of extract were determined by in vivo method on STZ induced diabetic rats. Antiadipogenic activity was determined by in vitro method on 3T3-L1 cell line in comparison to simvastatin as reference drug. Result. The extract showed significant fall in fasting serum glucose (FSG), that is, 234.68 and 211.61 mg/dL, in STZ induced diabetic animals for dose groups AS001 and AS002, respectively. The PL extract also exhibited noteworthy antiadipogenic activity on 3T3-L1 cell line. The value of inhibitory concentration (IC50) of PL extract to reduce adipocyte cells was found to be 662.14 μg/mL. Conclusion. The PL extract exhibited significant antiadipogenic, antidiabetic, and hypolipidemic activities.